Effect of Rudder Bulb Installation on Ship Propulsion Performance of Anchor Handling Design VS 491 CD during Towing Barge Operation - Harifuddin; I Made Ariana; Beny Cahyono (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
An anchor handling ship is a ship designed to support offshore operations in the form of handling offshore building anchors and carrying out activities of moving objects such as FPSO, Semi-Submersible Rigs, construction, production, and barges from one place to another where it requires bollard strength. pull which varies depending on the size of the object, besides that it is also to support other activities such as exploration and drilling. The VS 491 design type anchor handling tug supply (AHTS) vessel which has been built by a shipyard in Batam has a maximum bollard pull test of 255 tons. This paper will analyze the propeller thrust, power, and efficiency propeller before and after the installation of the Rudder Bulb (RB) respectively in free-running conditions and towing barge conditions in 50% barge conditions and full loaded capacity, as well as in draft, and Speed on certain Anchor Handling ships. The resistance of the object being towed (towing) will be calculated on the load and speed of each. By using Maxsurf, software Rhinoceros 3D, dan the Numeca CFD, the shape of the ship's hull is produced according to the original. Then validation is carried out by comparing the resistance in the calculation by Maxsurf/Holtrop and the resistance in the calculation by CFD where resulting in a difference of less than 5% so that it can be said that the form of the model is in accordance with the original shape of the ship. Based on the calculation results in the free running conditions of the Anchor Handling ship, the Propulsive Coefficient (Pc) without ESD Rudder-Bulb (RB) at speeds of 10, 12, and 16.36 knots is 0.5162, 0.5407, and 0.5769 respectively, while with ESD-RB each is 0.5008, 0.5417, and 0.5921. Comparison of the Propulsive Coefficient without ESD-RB and with ESD-RB, that at speeds of 12 and 16.36 knots, the Propulsive Coefficient (Pc) increased by 0.19% and 2.58%, respectively, but the Propulsive Coefficient (Pc) decreased by 3.08% at 10 knots. Based on the analysis that has been carried out, it indicates that the installation of the Rudder Bulb (RB) will give an increase in the Propulsive Coefficient (Pc) at speeds of 10 knots and above in free-running conditions, whereas when towing it hardly gives an increase in the Propulsive Coefficient (Pc).